OROPHARYNGEAL ADMINISTRATION OF MOTHER'S COLOSTRUM: A LITERATURE REVIEW - Jéssica Blatt Lopes; Luciana Dias de Oliveira; Betina Soldateli (Universidade do Estado do Rio de Janeiro, 2018)
Introduction: Premature births are considered a public health problem. Estimates indicate that approximately 30% of preterm newborns present complications inherent to this condition due to an immature immune response, as well as the immaturity of their digestive tract, which cause important long-term sequelae, such as growth deficit, delay in neurodevelopment, impairment of vision and hearing, with irreparable damage to children's health. Colostrum therapy is an admittedly safe technique that uses maternal colostrum to provide preterm infants with early immunological protection. This article aims to answer the following question: what is the impact of colostrum therapy on the health of premature infants? Objective: To review the evidence on the benefits of colostrum therapy for preterm infants. Methodology: Narrative review of the literature. The search for the articles was done in the databases of Pubmed, Cochrane, Virtual Health Library, Medline EBSCO, Proquest, Embase and Banco de Teses da Capes, without language restriction or publication period. Gray literature included unpublished theses, dissertations and abstracts. The descriptors used in the search strategy were: human milk, premature and colostrum. In addition, the terms "colostrum therapy", "colostrum oropharyngeal administration" and "colostrum oral administration" were used. Results: The results of nine studies were included in this review, being eight controlled and one observational. Different endpoints were measured in the studies, with approaches related to nutrition and growth, clinical outcomes, assessment of oral mucosa colonization of the newborn, and evaluation of immune development mediators, such as serum immunoglobulin A and lactoferrin secreted in the urine. When comparing the groups that received the colostrum with the control groups, the findings are positive, such as a shorter time to reach the full enteral diet, a higher mean weight at 36 weeks of life, a protective effect for sepsis development, and better breastfeeding rates at hospital discharge than children who did not receive colostrum therapy. Conclusions: Although there is no strong evidence of the clinical impact of colostrum therapy, it does not pose a risk for children. More evidence is needed on the impact of colostrum therapy on the prevention of clinical outcomes of higher incidence in premature infants to support the widespread implantation of this practice in neonatal units. DOI: 10.12957/demetra.2018.29813